Evaluating a worldwide wheat collection for resistance to Hessian fly biotype ‘Great Plains’ - Xu, Yunfeng; Ghori, Nida; Hussain, Shabbir; Xu, Xiaoting; Su, Zhenqi; Zhang, Dadong; Zhao, Lanfei; Liu, Xuming; Chen, Ming-Shun; Bai, Guihua (Frontiers in Plant Science, 2024)
Hessian fly (HF), Mayetiola destructor, is a major insect pest that causes severe losses in grain yield and quality of wheat (Triticum aestivum). Growing resistant cultivars is the most cost-effective approach to minimize wheat yield losses caused by HF. In this study, 2,496 wheat accessions were screened for resistance to the HF biotype ‘Great Plains’ (GP) in the greenhouse experiments. To purify seeds from heterogeneous resistant accessions, we recovered single resistant plants from 331 accessions that had at least one resistant plant after HF infestation of a global collection of 1,595 accessions and confirmed 27 accessions with high resistance (HR), and 91 accessions with moderate resistance (MR) to the GP biotype using purified seeds. Screening of 203 U.S. winter wheat accessions in three experiments identified 63 HR and 28 MR accessions; and screening of three additional Asian panels identified 4 HR and 25 MR accessions. Together, this study identified 96 HR accessions and 144 MR accessions. Analysis of the geographic distribution of these HR and MR accessions revealed that these countries with HF as a major wheat pest usually showed higher frequencies of resistant accessions, with the highest frequency of HR (81.3%) and MR (30.6%) accessions identified from the U.S.. In addition, phenotyping of 39 wheat accessions that carry known HF resistance genes showed that all the accessions except H1H2 remain effective against GP biotype. Some of these newly identified resistant accessions may contain new HF resistance genes and can be valuable sources for developing HF resistant wheat cultivars.